PEDIATRIC HEMORRHAGIC STROKE – ETIOLOGY, CLINICAL FEATURES AND OUTCOMES - Khakimov M.N., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Hemorrhagic stroke in children represents a rare but life-threatening neurological emergency. Unlike adult populations, pediatric hemorrhagic stroke is most commonly associated with structural vascular abnormalities and hematologic disorders. Early recognition and appropriate management are crucial for reducing morbidity and mortality. This article provides an overview of the etiology, risk factors, clinical presentation, diagnostic strategies, and outcomes of pediatric hemorrhagic stroke.